Five new species and three new varieties of Begonia section Casparya endemic to Colombia - Jara-Muñoz, Orlando Adolfo; Richardson, James E.; Zabala-Rivera, Juan Carlos (Phytotaxa, 2021)
Casparya, one of the most species-rich sections of Begonia in the Neotropics with 44 species, is distributed from Costa Rica to Peru, with the highest diversity in the Colombian Andes. The section is morphologically well-differentiated and can be distinguished from other Andean cane-like begonias by the 3-horned fruit and multifid or un-divided styles. Here we describe eight taxonomic novelties for Casparya from Colombia, five species and three varieties, descriptions include illustrations, distribution maps, taxonomic comments, and assessments of conservation status. The five species described here are: Begonia diegoi, Begonia galeanoi, Begonia mamapachensis, Begonia perijaensis, and Begonia vinagrera; and the three new varieties are: Begonia kalbreyerii var. orquidensis, Begonia silverstonei var. brevipetiolata, and Begonia vinagrera var. pomecensis. We also present a taxonomic key for the 32 species of Casparya so far known from Colombia.